Analisis Tingkat Keterampilan Literasi Informasi Mahasiswa Program Studi Ilmu Perpustakaan Dan Informasi Islam UIN Sayyid Ali Rahmatullah Tulungagung Berdasarkan Standar Association Of College And Research Libraries (ACRL) - Dewi Iklima; Nurul Setyawati Handayani (UIN Mataram, 2025)
Information is a basic need in student life which is needed, of course, of a scientific nature. In order to fulfill this information, students are required to have information literacy skills. This is done to make it easier for students to collect and find information according to their needs. This research aims to determine the level of information literacy of Islamic Library and Information Science students at UIN Sayyid Ali Rahmatullah Tulungagung using ACRL (Association of College and Research Libraries) standards. This type of research uses descriptive with a quantitative approach. The population in this study was 167 Islamic Library and Information Science students at UIN Sayyid Ali Rahmatullah Tulungagung Class of 2020 and 2021. The sampling technique used was nonprobability sampling with the Slovin formula so that 63 samples were obtained. The data analysis technique is by looking for percentages using the SPSS version 26 program. The results of the research show that Islamic Library and Information Science students at UIN Sayyid Ali Rahmatullah Tulungagung are based on ACRL standards with 5 indicators, namely determining the nature and scope of information needed, accessing information effectively and efficient, evaluating information and its sources critically, using information for specific purposes, understanding economic, legal and social aspects related to the use of information, getting a final score of 4.04, which means that the level of information literacy skills is good